Measurement of the Applicability of Abdominal Point-of-Care Ultrasound to the Practice of Medicine in Saudi Arabia and the Current Skill Gaps - Rajkumar Rajendram; Mamdouh Souleymane; Naveed Mahmood; Rakan Sambas; Yousuf M.S. Kharal (CINQUILL Medical Publishers Inc., 2021)
Background: Renal, gastrointestinal, and hepatic pathology, and the resources available for their management vary internationally. Whilst abdominal point-of-care ultrasound (APOCUS) should enhance management, uptake by physicians, worldwide, has been poor. So, the aim of this study was to explore the applicability of APOCUS to medical practice in Saudi Arabia, residents' current ability to perform APOCUS, and the skill gaps. Methods: A validated questionnaire was distributed to the internal medicine residents at our institution to determine their ability to perform APOCUS (self-reported), and obtain their opinions on its applicability for the detection of hepatomegaly, splenomegaly, hydronephrosis, and ascites. Statistical analysis: Standard descriptive statistical techniques were used. Categorical data, presented as frequency, were compared using the χ2 test. The Likert scale responses, presented as mean ± standard deviation, were compared with a t test or analysis of variance. Results: Ninety-eight residents participated (response rate 90.7%). Abdominal POCUS is very applicable to their practice. The use of APOCUS to detect ascites was the most applicable (mean 4.61 ± SD 0.69). However, proficiency in APOCUS was poor (mean 1.65 ± SD 1.11). Conclusions: The difference between internists' self-reported ability to perform APOCUS and its perceived usefulness demonstrates a skill gap. Thus, whilst APOCUS is applicable to medical practice in Saudi Arabia, significant skill gaps exist.